Entrepreneurship dalam Lingkungan Sekolah di SMA PGRI 4 Palembang - Neta Dian Lestari; Diana Widhi Rachmawati; Erma Yuliani; Nova Pratiwi; Ida Suryani; Chandra Kurniawan; Januardi Januardi; Boby Agus Yusmiono; Hendri Gunawan; Riswan Aradea (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2019)
ABSTRACTThe purpose of community service activity is to instill the spirit of "Entrepreneurship in a school environment especially on students in SMA PGRI 4 Palembang". The material is delivered by dividing participants into two classes. The speaker who delivered the material was FKIP lecturer from Palembang PGRI University. After explaining the material by the speakers, participants were asked to carry out entrepreneurship practices. The result of this activity as interest and knowledge of participants about entrepreneurship are increases.Â Keywords: Entrepreneurship, knowlegde, school environment.Â ABSTRAKTujuan kegiatan pengabdian kepada masyarakat ini adalah untuk menanamkan jiwa â€œEnterpreneurship dalam lingkungan sekolah terutama pada siswa di SMA PGRI 4 Palembangâ€. Materi disampaikan dengan cara membagi peserta menjadi dua kelas. Narasumber yang menyampaikan materi adalah dosen FKIP universitas PGRI Palembang. Setelah penjelasan materi oleh narasumber, peserta diwajibkan untuk melakukan praktik kewirausahaan. Hasil kegiatan ini menunjukkan bahwa animo dan pengetahuan peserta tentang kewirausahaan meningkat.Â Kata Kunci: Kewirausahaan, pengetahuan, lingkungan sekolah.Â